The effects of arbuscular mycorrhizal fungi (Glomus mosseae sp.) inoculation on aerobic paddy growth performance and root's nutrient (phosphorus) / Muhammad Inamul Husin Jasni - Husin Jasni, Muhammad Inamul (Faculty of Plantation and Agrotechnology, 2015)
This research was done by inoculated Arbuscular Mycorrhizal fungi (Glomus mosseae sp.) with aerobic paddy to observe the effect of the fungi whether it can boost the growth performance and nutrient uptake (phosphorus), since its' lack of growth performance and nutrient uptake (phosphorus) compare to lowland paddy. The other objective of this research was to find the least amount of mycorrhizae needed to increase the growth performance and nutrient uptake (phosphorus) by Aerobic paddy. The research was done by applying different rate of mycorrhizae which is l0gram, 20gram and 30gram to aerobic paddy seedling. All the treatment has 4 replication. The research was done inside greenhouse and all the paddy was plant inside pot. The data was taken from week 5 until week 11 of aerobic paddy. The data taken was the height of paddy, the number of paddy leave and tiller, the fresh weight of root, the dry matter of stem,leave and root, the leaf area (cm²), the number of phosphorus obtain and lastly the presence of Mycorrhizae colonization on root. The b result shows that all the treatment shows significance of difference (P<O.05) after the data being analyzed by ANOVA calculation . The mycorrhizae were presence on the root after being observed under Trinocular microscope. The conclusion from the research was Arbuscular mycorrhizae can enhance the growth performance and nutrient uptake (phosphorus) for aerobic paddy.